2014
DOI: 10.1515/jpem-2013-0342
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of pediatric Graves’ disease

Abstract: Long-term remission rates of pediatric onset GD with ATDs are very low, especially with longer follow-up. Higher pretreatment free T4 and high TRAB titers predict need for definitive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 10 publications
2
20
1
2
Order By: Relevance
“…The proportion of boys in this study does not differ significantly from the proportions found in previous studies [8, 10, 12, 18] and it did not change between the first and the second 10-year study periods.…”
Section: Discussioncontrasting
confidence: 67%
“…The proportion of boys in this study does not differ significantly from the proportions found in previous studies [8, 10, 12, 18] and it did not change between the first and the second 10-year study periods.…”
Section: Discussioncontrasting
confidence: 67%
“…Studies in adults and children have taught us that the initial severity and course of the disease are highly variable and that relapse rates are higher in children than that in adults, with remission occurring in 20-30% in children and 40-60% of adults after a first course of treatment lasting a median of 2 years (3,24,31,32,33,34,35,36,37,38,39). Relapse occurs within 6 months of the end of drug treatment in 75% of patients, whereas only 10% of patients present a relapse more than 18 months after the end of the treatment (36,40,41).…”
Section: Outcomementioning
confidence: 99%
“…They also tend to present the biases inherent to observational design, with most studies retrospective, with a limited number of patients enrolled, many of whom are lost to follow-up, and large amounts of missing data. The main pediatric cohort studies are summarized in Table 1 (3,27,31,32,33,34,35,36,37,38,39,40,49). The comparative effectiveness of treatment with ATD, as characterized by the remission rate (the definition of which differs between studies), varied from 11 to 49% with treatment most effective for the longer duration of treatment with ATD in two large independent cohorts, with no fatal side effects reported (27,40).…”
Section: Recent Findings From Studies In Childrenmentioning
confidence: 99%
“…Персистенция тирео-токсикоза на фоне лечения тиреостатиками нередко приводит к развитию эндокринной офтальмопатии [4]. После прекращения терапии тиреостатиками реци див возникает у 10-90% (в среднем у 60-75%) пациентов, чаще всего рецидив тиреотоксикоза про-воцируется стрессом и беременностью, но может возникать идиопатически [7,8].…”
Section: актуальностьunclassified